The action of fillers in the enhancement of the tribological performance of epoxy composite coatings - Balázs Jakab; Ileana Panaitescu; Norbert Gamsjäger (Polymer Testing, 2021)
The addition of reinforced material (polymer and mineral fillers) to epoxy resin matrices results in the improvement of the overall performance of the composite, allowing the application of these materials as tribo-materials in industrial applications. Enhancement of the tribological properties (low friction coefficient, increased wear resistance and non-stick properties) of epoxy coatings is done by embedding fillers with various particle sizes and with different filler volume fractions. The aim of this work is to determine the factors influencing the wear-reducing mechanisms of the fillers. This was done by wear tests carried out on a pin-on-disc apparatus and on a Taber Abraser device. A significant decrease in the wear rate was recorded with the formulations containing polymer fillers such as polytetrafluoroethylene (PTFE), polyethylene (PE) and fluorinated ethylene propylene (FEP), due to their self-lubricating nature. The particle size of silica (SiO2) fillers was found to play a significant role, coarse particles reducing the wear rate due to the bond at the resin/filler interface. It was shown that not all fillers helped improving the wear resistance; the SiO2 fillers with lower particle size had a negative effect on the wear resistance of the epoxy coating, by causing discontinuities in the material. The worn surfaces were analyzed using light microscopy and scanning electron microscope (SEM), to help better understand the wear mechanisms involved.